An animal model recapitulates human hepatic diseases associated with GATA6 mutations - Wenpeng Shi; Xiaogui Yi; Hua Ruan; Donglei Wang; Dan Wu; Pengfei Jiang; Lisha Luo; Xirui Ma; Faming Jiang; Cairui Li; Weinan Wu; Lingfei Luo; et al. (Proceedings of the National Academy of Sciences, 2025)
Heterozygotic GATA6 mutations are responsible for various congenital diseases in the heart, pancreas, liver, and other organs in humans. However, there is lack of an animal that can comprehensively model these diseases since GATA6 is essential for early embryogenesis. Here, we report the establishment of a gata6 knockout zebrafish which recapitulates most of the symptoms in patients with GATA6 mutations, including cardiac outflow tract defects, pancreatic hypoplasia/agenesis, gallbladder agenesis, and various liver diseases. Particularly in the liver, the zebrafish gata6 model exhibits the paucity of intrahepatic bile ducts, disrupted bile canaliculi, cholestasis, resembling the liver diseases associated with GATA6 mutations. Moreover, an unreported phenotype, hepatic cysts, has been also revealed in the model. Mechanistically, Gata6 interacts with Hhex and binds lrh-1 promoter to synergistically activate its expression, thereby enhancing the Lrh-1-mediated β-catenin signaling which is essential for liver development. This transcriptional activation of lrh-1 is tightly controlled by the negative feedback, in which Lrh1 interacts with Gata6 to weaken its transactivation ability. Moreover, Gata6 level is regulated by Hhex-mediated proteasomal degradation. The orchestration by these three transcription factors precisely modulates Gata6 activity, ensuring β-catenin signaling output and proper liver development in zebrafish. Importantly, the molecular mechanism identified in zebrafish is conserved in human cells. GATA6 mutant variants associated with hepatobiliary malformations in humans interact aberrantly with HHEX, resulting in subsequent impairments of LRH-1 activation. Conclusively, the disease model established here provides both phenotypic and mechanism insights into the human hepatic diseases associated with GATA6 mutations.